2017
DOI: 10.1021/acsomega.7b00657
|View full text |Cite
|
Sign up to set email alerts
|

Bioimaging Application and Growth-Promoting Behavior of Carbon Dots from Pollen on Hydroponically Cultivated Rome Lettuce

Abstract: Carbon dots (CDs) obtained from rapeseed pollen with a high production yield, good biocompatibility, good water solubility, low cost, and simple synthesis are systematically characterized. They can be directly added to Hoagland nutrient solution for planting hydroponically cultivated Lactuca sativa L. to explore their influence on the plants at different concentrations. By measuring lettuce indices of growth, morphology, nutrition quality, gas exchange, and content of photosynthetic pigment, amazing growth-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 46 publications
4
55
0
Order By: Relevance
“…The enhancement of chlorophyll content is beneficial for harnessing more light energy in photosynthesis. These data prove that CDs have low phytotoxicity and exhibited negligible effect on the physiological metabolism, CD‐induced enhancement in chlorophyll content enables plants to absorb more light energy, which is consistent with our previous studies on the phytotoxicity of CDs in plants …”
Section: Resultssupporting
confidence: 92%
“…The enhancement of chlorophyll content is beneficial for harnessing more light energy in photosynthesis. These data prove that CDs have low phytotoxicity and exhibited negligible effect on the physiological metabolism, CD‐induced enhancement in chlorophyll content enables plants to absorb more light energy, which is consistent with our previous studies on the phytotoxicity of CDs in plants …”
Section: Resultssupporting
confidence: 92%
“…Zheng et al, for example, reported that a 25-day exposure of 10-30 mg/L of CQDs, obtained from rapeseed (Brassica napus) pollen, to hydroponically grown Rome lettuce (Lactuca sativa) improved plant growth. The mechanism was suggested to be through an increase in leaf number and foliar area [35]. They also reported that the 20 mg/L CQD treatment reduced nitrate content in leaves; suggesting that the CQDs The terminal sink for all pollutants, the aquatic ecosystem, plays important roles in the full life cycle of ENMs due to their intentional and unintentional release [22].…”
Section: Discussionmentioning
confidence: 99%
“…The indicators of shoot weigh (fresh and dry) were measured and the data of 4 random plant averaged, while the rest of indicators are obtained for 4 times. All indicators are gauged according to previously disclosed methods [27,28] .…”
Section: Plant Cultivationmentioning
confidence: 99%